Artificial Intelligence and the Digital Transformation of Archival Systems: A Bibliometric Study - Arum Suryaningtyas; Tony Wijaya (STIE Amkop Makassar, 2025)
The integration of Artificial Intelligence (AI) in digital archive management has become increasingly important in response to growing demands for efficiency, accessibility, and information preservation in the digital transformation era. This study analyzes the development of research related to this theme through a bibliometric approach based on Scopus data and visualizations using VOSviewer. The results reveal a surge in publications since 2020, driven by accelerated digitalization following the pandemic and the emergence of generative AI technologies such as ChatGPT. Countries such as the United States, China, and the United Kingdom dominate scholarly contributions, although institutions from developing nations like the University of South Africa also play a strategic role. Bibliometric visualizations show that AI serves as a central node closely linked to terms such as digital archives, metadata, sustainability, and ethical technology. Research evolution is shifting from technical focuses toward ethical, social, and sustainability issues. Despite the significant growth in literature, challenges remain, including gaps in global collaboration, the lack of ethical frameworks, and limited technological literacy. This study highlights the importance of interdisciplinary collaboration and the development of equitable digital policies in building sustainable intelligent archival systems.